Strategies for off season production of Coleus in the Southern zone of Kerala - Anju V S (Department of Agronomy, College of Agriculture, 2014)
A field experiment entitled “Strategies for off season production of coleus in the southern zone of Kerala” was undertaken at Instructional Farm, College of Agriculture, Vellayani from November 2013 to May 2014. The objectives of the study were to fix the ideal time of planting and nutrient management for off season production of coleus var. Suphala and to work out the economics of cultivation. The treatments consisted of four dates of planting (d1-November 15; d2-December 1; d3-December 15 and d4-January 1) and three nutrient management practices (n1-Recommended dose - 60:60:100 kg NPK ha -1 through fertilizers; n2-RD through organic manures -6 t farmyard manure + 3 t coir pith compost + 3 t wood ash per ha+ PGPR mix1 and n3-Modified nutrient dose -60:30:120 kg NPK ha -1 through fertilizers). The experiment was laid out in split plot design assigning dates of planting in main plots and nutrient management practices in sub plots with four replications. A uniform dose of FYM @ 10 t ha-1 of and of neem cake @ 1 t ha-1 was applied to all plots. Among four dates of planting tried, planting on November 15 (d1) recorded taller plants, higher number of branches and leaves per plant and higher leaf area index. Yield components like number and weight of tubers per plant were maximum when planted on November 15 (d1) followed by planting on December 1 (d2). Number and weight of marketable tubers per plant showed a decreasing trend when planting was delayed beyond November. The tuber yield also exhibited a similar trend recording the highest tuber yield of 14.89 t ha-1 for November 15 planting and the lowest tuber yield of 10.71 t ha -1 for January 1 planting. The tuber yield was significantly and positively correlated with the total rainfall received during the cropping period. Planting on November 15 recorded the highest utilization index. Total dry matter production and uptake of N, P and K were maximum when the crop was planted on November 15 and it showed a declining trend due to late planting. But quality attributes of tuber were not significantly influenced by date of planting. The highest net income (Rs.167525 ha -1) and BCR (1.84) were obtained by planting on November 15, which decreased with delay in planting. Modified nutrient dose of 60:30:120 kg NPK ha-1 through fertilizers (n3) significantly promoted all the growth characters. Higher number and weight of tubers as well as marketable tubers per plant were recorded by the same treatment which resulted in the highest tuber yield of 14.36 t ha -1. The same trend was noticed in the case of total dry matter production, utilization index, uptake of nutrients and starch content of the tuber. Significantly higher net income (Rs.163900 ha -1) and BCR (1.84) were recorded by the modified nutrient dose (n3) followed by recommended dose of nutrients through fertilizers (n1). Regarding interaction effects, November 15 planting with modified nutrient dose recorded significantly taller plants with higher leaf area index during later stages of crop growth. Similarly, the same interaction produced the highest number of marketable tubers per plant and tuber yield. November 15 planted crop with modified nutrient dose registered the highest net income and benefit cost ratio. Soil analysis after the experiment indicated higher pH and organic carbon contents and lower available N, P and K contents in organically manured plots than fertilizer applied plots. The study revealed that for off season production of coleus var. Suphala in the southern zone of Kerala, the ideal time of planting is November 15 which recorded higher tuber yield, net income and benefit cost ratio. Modified nutrient dose of 60:30:120 kg NPK ha-1 through fertilizers + FYM @ 10 t ha-1 + neem cake @ 1 t ha-1 can be recommended for the crop for getting higher tuber yield, net income and benefit cost ratio.